The rapid detection of a neonatal unit outbreak of a wild-type Klebsiella variicola using decentralized Oxford Nanopore sequencing - Rhys T. White; Michelle Balm; Megan Burton; Samantha Hutton; Jamaal Jeram; Matthew Kelly; Donia Macartney-Coxson; Tanya Sinha; Henrietta Sushames; David J. Winter; Maxim G. Bloomfield (Antimicrobial Resistance and Infection Control)
Abstract Background Klebsiella variicola has been implicated in neonatal intensive care unit (NICU) outbreaks previously and can be misidentified as Klebsiella pneumoniae. An increased incidence of K. pneumoniae bacteremia on the NICU of our institution was notified to the infection prevention and control (IPC) team in May 2024. The four isolates involved displayed wild-type susceptibility, so had not been detected via multidrug-resistant organism surveillance. This triggered investigation with a nanopore-based decentralized whole-genome sequencing (dWGS) system in operation at our laboratory. Methods Since early 2022, the hospital laboratory at Wellington Regional Hospital has been performing dWGS using the Oxford Nanopore MinION device. This allows for prospective genomic surveillance of certain hospital-associated organisms, but also rapid reactive investigation of possible outbreaks. Isolates are sequenced in the hospital laboratory and undergo multilocus sequence typing (MLST). If transmission events are suspected, sequence data are transferred to the reference laboratory, the Institute for Environmental Science and Research (ESR) for high-resolution bioinformatic analysis. Results Within 48 h of notification isolates had been subcultured and sequenced. This showed that three of four isolates were in fact K. variicola, and two of these were sequence type (ST)6385. This sequence type had not been seen previously at our institution, so transmission was suspected. Environmental sampling revealed K. variicola ST6385 in two sink traps on the unit, and prospective sequencing of all K. pneumoniae isolates from NICU samples revealed two further infants with K. variicola ST6385. Subsequent phylogenetic analysis at ESR using original sequence data showed tight clustering of these isolates, confirming an outbreak. Sink traps were disinfected, environmental cleaning procedures were updated, and a strict focus on hand hygiene was reinforced on the ward. No further isolates were detected, and the outbreak was closed after two months. Conclusions Access to dWGS at the level of the local hospital laboratory permitted rapid identification of an outbreak of an organism displaying no unusual antimicrobial resistance features at a point where there were only two known cases. This in turn facilitated a rapid IPC response.